2020
DOI: 10.33824/pjpr.2020.35.4.36
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Communication, Teamwork Effectiveness, and Organizational Commitment in Pakistani Nurses

Abstract: The current study was focused on identifying how interpersonal communication affects teamwork effectiveness and organizational commitment in nurses. The sample of (N = 150) nurses were recruited through purposive sampling technique from a public hospital of Lahore. To test the study assumptions, Socio- Communicative Orientation Scale (Richmond & McCroskey, 1990), Teamwork Effectiveness Self-Assessment Questionnaire (Sterling & Selesnick, 1988), and Organization Commitment Scale (Allen & Meyer, 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This finding is consistent with previous studies by Liao and Liu (2019) Finally, this study also found that interpersonal communication plays a vital role as a mediator of the effect of PsyCap on teachers' organizational commitment. This evidence, in line with previous studies, concluded that PsyCapinfluences interpersonal communication (Liao & Liu, 2019) and interpersonal communication affects organizational commitment (e.g., Anitra&Astuti, 2020;Hutagalung, 2020;Susita et al, 2020;Farooqi et al al., 2020;Junaidi, 2021). Moreover, it produces empirical models regarding the indirect effect of PsyCap on organizational commitment mediated by interpersonal commitment.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This finding is consistent with previous studies by Liao and Liu (2019) Finally, this study also found that interpersonal communication plays a vital role as a mediator of the effect of PsyCap on teachers' organizational commitment. This evidence, in line with previous studies, concluded that PsyCapinfluences interpersonal communication (Liao & Liu, 2019) and interpersonal communication affects organizational commitment (e.g., Anitra&Astuti, 2020;Hutagalung, 2020;Susita et al, 2020;Farooqi et al al., 2020;Junaidi, 2021). Moreover, it produces empirical models regarding the indirect effect of PsyCap on organizational commitment mediated by interpersonal commitment.…”
Section: Resultssupporting
confidence: 90%
“…Organizational commitment is also influenced by interpersonal communication. Previous studies proved that interpersonal communication affects organizational commitment (e.g., Syaekhu, 2018;Ghofar et al, 2018;Anitra&Astuti, 2020;Hutagalung, 2020;Susita et al, 2020;Farooqi et al, 2020;Junaidi, 2021). It indicates that interpersonal commitment is an antecedent of organizational commitment.…”
Section: Interpersonal Communication and Teachers' Organizational Com...mentioning
confidence: 92%
See 1 more Smart Citation
“…Por otro lado, la eficacia del equipo esta parcialmente vinculada con el compromiso laboral. Además, el estudio reveló que la comunicación interpersonal puede desempeñar un papel destacado en el desarrollo del compromiso laboral, por lo que hay que esforzarse para mejorar y potenciar las habilidades de comunicación interpersonal en las organizaciones (Farooqi et al, 2020).…”
Section: Beneficios De La Comunicación Interna En Las Organizacionesunclassified
“…The Corn-Sat Inventory has been extensively employed within the communication industry, which implies that satisfaction is a crucial factor in the communication field. According to Farooqi et al [20] , interpersonal communication satisfaction (IPS) encourages employees to accomplish shared goals and has a positive correlation with organisational commitment. Jia et al [21] also claimed that positive work experiences of employees encourage them to satisfy their superior's relationship-oriented requirements.…”
Section: Research Objectivesmentioning
confidence: 99%